Infaq and Shadaqah as a Source of Original Regional Income in Aceh (Case Study in Bireuen Regency, Pidie and Lhokseumawe City) - Syahbandir, Mahdi; Mahfud, Mahfud; Rizki, Muhammad; Wahyu, M. Arizka; Akhyar, M. Nur (Journal of Governance and Social Policy, 2023)
Article 21 (2) of Qanun Aceh Number 10, 2007 on Baitul Mal provides that "a person or an institution which is not obliged as muzakki may pay infak to Baitul Mal. Article 180 (1) of Aceh Governance Act, provides that Aceh original revenue souces and regional revenue sources excludes infak and shadaqah as original regional revenues. Legal basis of collecting infak and shadaqah is very weak as it is only based on the Head of District/Major Regulation. The research shows that the collection of the doation in Kabupaten Bireuen is done based oon Bireuen's Head of District Regulation Number 20, 2013 on the Mechanism of Zakat, Infaq, Shadaqah and Other Religious Assets Management, in Lhokseumawe it is done with the Major Regulation Number 33, 2017 on the Mechanism of Zakat, Infaq, Shadaqah, Waqf and Other Religious Assets and in Pidie District is done with the Head of Pidie's District Regulation Number 11, 2016 on the Mangement of Infaq and Shadaqah in Pidie District by referring to Qanun Aceh Number 10, 2007 regarding Baitul Mal.